Quality Control Using Fishbone Analysis Method to Improve Product Quality in Dya Bordir Tasikmalaya - Salma Hakim, Nadhira Tsaniya; Barlian , Barin; Lestari , Suci Putri (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this research is to find out how to control product quality on products DYA Bordir Tasikmalaya. In this study using data collection methods with techniques in the form of interviews, observation, and documentation. The analysis tool is carried out using the Fishbone Analysis method. The results of the analysis on the Pareto diagram show that the defective products are mostly caused by loose threads and twisted threads. From the results of the analysis of the causal diagram it is also seen that the factors causing production defects come from human factors, machines, methods and raw materials. It is recommended for DYA Bordir Tasikmalaya to be able to continue to improve products or minimize product defects that occur. By utilizing the Fishbone Analysis method to identify and find solutions to improve product quality.